Evaluation of methanolic extract of Phragmites karka on carbon tetrachloride-induced liver fibrosis in rat (Bangladesh Journal of Pharmacology, 2017)
Phragmites karka has been reported for its anti-inflammatory and analgesic activities. Here, extracts of leaf and rhizome of the plant were individually investigated in CCl4-induced hepatofibrosis in male Wistar rats by administering CCl4 intraperitoneally biweekly for 6 weeks.  Afterwards the animals were investigated for liver fibrosis at biochemical, molecular and histological levels, and it showed a profound increase (p